Hubungan Antara Job Demands Dengan Work Engagement Pada Karyawan Bank Muamalat KC Medan Balaikota - Widya Chandra Dewi; Maqhfirah Maqhfirah (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2026)
This study aims to look at the relationship between job demands and work engagement in employees with a quantitative approach to the type of correlation research. The population in this study were 30 employees in the finance operations division. The research sample also amounted to 30 people with a total sampling technique. Based on the results of data analysis using the correlational analysis method, it is known that there is a significant negative relationship between job demands and work engagement, seen from the coefficient value (Rxy) = -0.703 with p = 0.000 0.050. In this study, job demands for employees are classified as moderate, based on the empirical average value obtained (50.967) which is smaller than the hypothetical average value (60). Furthermore, it is known that work engagement among employees is high, this is based on the empirical average value obtained (46.267) which is greater than the hypothetical average value (40). Likewise with the coefficient of the term (R2) which has a value of 0.494, this is equivalent to 49.40%, which means that job demands contribute 49.40% to work engagement among employees.